Relationship Between Responsible Leadership and Caring Behaviors of Nurses: the Mediating Role of Organizational Pride - Mohammad Mehdi Mohebi; Khalil Zandi; Hamid Kiany Fotovat (Hamadan University of Medical Sciences, 2022)
Background and Objective: Care is a fundamental aspect of nursing services. To identify the effective factors in the promotion of caring behaviors of nurses, this research aimed to analyze the relationship between responsible leadership and caring behaviors of nurses with mediating role of organizational pride. Materials and Methods: The present descriptive-correlation research was performed on a statistical population consisting of 470 nurses in Besat hospital, Hamadan, Iran. The statistical sample included 240 nurses who were selected using the simple random sampling method. Data collection tools were responsible leadership questionnaires (Doh et al., 2011), organizational pride (Nouri et al., 2017), and the caring behaviors of nurses (Wolf et al., 1998). The collected data were analyzed using Pearson's correlation test and structural equation modeling. The software used for data analysis were SPSS (version 16) and Lisrel (version 8.5). Results: Based on the findings, there was a positive and significant relationship between responsible leadership and the caring behaviors of nurses (r=0.373). The relationship between responsible leadership and organizational pride was positive and significant (r=0.706). Moreover, there was a positive and significant relationship between organizational pride and caring behaviors (r=0.592). The direct effect of responsible leadership on the caring behaviors of nurses was not significant (p>0.05). However, the direct effect of responsible leadership on organizational pride was significant (p<0.05). Besides, the direct effect of organizational pride on caring behaviors was significant (p<0.05). Conclusion: Finally, the indirect effect of responsible leadership on the caring behaviors of nurses through organizational pride was significant.